(untitled) (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The aim of this study is to inspect the ameliorative effect of avenanthramides (AVA) on CP nephrotoxicity in Sprague-Dawley rats. Materials and Methods: Blood samples were collected for the determination of hematological parameters. Creatinine, blood urea nitrogen (BUN), and tumor necrosis factor-α (TNF-α) were measured in serum. Specimens from both kidneys were taken for histopathological examinations. Results: Administration of AVA resulted in significant decrease in the level of creatinine and TNF-α when compared with CP group. Histopathologically, CP-induced vacuolar degeneration and necrosis of the kidney tubules. Administration of AVA ameliorates the histopathological alterations induced by CP. Conclusion: AVA can be considered as a protective agent for kidneys during administration of CP. The protective effect of AVA may be related to the reduction of TNF-α which implicated in the pathogenesis of CP nephrotoxicity. J. Adv. Vet. Anim. Res., 6(4): 521-527, December 2019